Increased risk of endometriosis by long term exposure to xenoestrogens: A case control study in Iranian women - Heydeh Keyhan; Sepideh Arbabi Bidgoli; Abolfazl Mehdizadeh Kashi (Islamic Azad University, 2016)
Aims of the study: Endometriosis is a prevalent gynecologic disorder in young women at reproductive age but the underlying risk factors have not identified yet in Iran and other neighboring countries. Persistent exposure to environmental endocrine disrupting chemicals (EDCs) in particular dioxins, PAHs and polychlorinated biphenyls (PCBs) with xenoestrogenic potentials have been hypothesized in the etiopathogenesis of endometriosis .We aimed in the present study to investigate the joint effects of endogenous and exogenous sources of estrogens on the incidence of endometriosis in Iranian women who born and lived in Tehran .Methods: The age matched study population consisted of 34 women with endometriosis and 100 healthy women who underwent surgery from March 2009 to March 2012 . Results: Out of evaluated exogenous sources of estrogen exposure, living near xenoestrogen producing factories (p<0.001*, OR= 16.8, CI 95%5-56.8) in women with lower economical status (p= 0.001, OR=8.29 Cl95%, 3.37-20.37) was identified as the most important risk factor of endometriosis. The prevalence of this phenomenon was higher in women with histories of malignancy in their first degree family (P=0.014, OR=3.08, CI95% 1.23-8.53), infertility (p<0.001, OR=13.07, Cl95%, 5.14-33.23), hormonal dysregulations (p=0.003, OR=8.38, CI95%, 2.03-34.61) and bipolar disorders (p=0.046, OR=3.44, CI95%, 1.11-10.68). Conclusion: Incidence and development of endometriosis is dependent on long term exposure to environmental xenoestrogens especially in women with lower economical status which may affect the endogenous levels of estrogen in women with background factors.